Anti-GD2 antibody dinutuximab inhibits triple-negative breast tumor growth by targeting GD2+ breast cancer stem-like cells. Issue 3 (15th March 2021) - Ly, Stanley; Anand, Vivek; El-Dana, Fouad; Nguyen, Khoa; Cai, Yiming; Cai, Shirong; Piwnica-Worms, Helen; Tripathy, Debasish; Sahin, Aysegul A; Andreeff, Michael; Battula, Venkata Lokesh
Abstract : Background: Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype with no effective standard therapy. Breast cancer stem-like cells (BCSCs) in primary TNBCs are reported to be responsible for metastatic spread of the disease and resistance to chemotherapy, but no available therapeutic tools target BCSCs. We previously reported that the ganglioside GD2 is highly expressed on BCSCs and that inhibition of its expression hampers TNBC growth. We therefore hypothesized that the anti-GD2 antibody dinutuximab (ch14.18) targets GD2 + BCSCs and inhibits TNBC growth. Method: To test our hypothesis, we first determined GD2 expression via immunohistochemistry in frozen primary tumor samples from patients with TNBC (n=89). Then, we examined the effects of dinutuximab on TNBC cell adhesion, migration, and mammosphere formation in vitro and on tumor growth in vivo using TNBC cell-line and patient-derived xenograft (PDX) models. Results: We found that GD2 was expressed in around 60% of primary TNBC tumors at variable levels and was associated with worse overall survival of patients with TNBC (p=0.002). GD2 was found to be expressed in tumors and stroma, but normal ducts and lobules in adjacent tissues have shown low or no GD2 staining, indicating that GD2 is potentially a novel biomarker for tumor and its microenvironment. Treatment with dinutuximab significantly decreased adhesion and migration of MDA-MB-231 and SUM159 TNBC cells. Moreover, dinutuximab treatment inhibited mTOR signaling, which has been shown to be regulated by GD2 in BCSCs. Dinutuximab also reduced tumor growth in nude mice bearing TNBC cell-line xenografts. Finally, dinutuximab in combination with activated natural killer cells inhibited tumor growth in a TNBC PDX model and improved overall survival of tumor-bearing mice. Conclusions: Dinutuximab successfully eliminated GD2 + cells and reduced tumor growth in both in vivo models. Our data provide proof-of-concept for the criticality of GD2 in BCSCs and demonstrate the potential of dinutuximab as a novel therapeutic approach for TNBC.